Nexus of Migration, Population and Economic Growth: The Case of Vietnam - Hoa, Pham Xuan; Xuan, Vu Ngoc; Thu, Nguyen Thi Phuong (Migration Letters, 2023)
This paper investigates the intricate interplay between migration patterns, population dynamics, and economic growth in Vietnam. The report uses data from the World Bank from 2000 to 2022. The unrestricted fixed and random panel data method is used in the study. As a nation with a rich history marked by economic transformations and demographic shifts, understanding the nexus of these three elements is paramount. The study employs a multidisciplinary approach, combining demographic analyses, economic indicators, and migration patterns to unravel the nuanced connections. The research aims to shed light on the impact of migration on population structure and its subsequent implications for economic development. By examining historical trends and current data, the paper seeks to provide insights into policy considerations for sustainable economic growth in Vietnam. The findings contribute to the broader discourse on the role of migration in shaping demographic landscapes and influencing economic trajectories. Through this exploration, the paper enriches the academic understanding of these dynamics and offers practical implications for policymakers navigating the complex terrain of national development in Vietnam.